Truth from the Valley : a practical primer on IT management for the next decade - Settle, Mark (Chief information officer) (New York, NY : Routledge/Bibliomotion, 2020)
"Management challenges faced by IT leaders in Silicon Valley will eventually be encountered by IT leaders everywhere. Successful Silicon Valley firms operate in radically different ways when compared with their conventional Fortune 500 counterparts. Valley firms rely almost exclusively on cloud-based business applications and cloud-computing resources to conduct daily business. In addition, they are increasingly relying on artificial intelligence and machine-learning tools to extract business information from vast quantities of data. Valley firms are operating on the leading edge of the changes taking place within the IT industry. In some cases, they are literally defining the leading edge of such changes! Truth from the Valley provides insight into ways in which people, process, and technology management challenges have been addressed by IT leaders in Silicon Valley. This book provides a comprehensive portrayal of the trends that will shape IT management practices in the next decade, and it challenges its readers to find ways of converting these challenges into opportunities that will enable their organizations to become more efficient, more impactful, and more business relevant in the future"--
Preface. About the Author. Introduction. Chapter 1: People. Chapter 2: Process.Chapter 3: Technology.Epilogue. Abbreviation Glossary.
OCLC-licensed vendor bibliographic record.
Keywords: Information technology -- Management; BUSINESS & ECONOMICS / Information Management; TECHNOLOGY / General; BUSINESS & ECONOMICS / Production & Operations Management